2016
DOI: 10.18006/2016.4(spl-3-adpciad).s116.s122
|View full text |Cite
|
Sign up to set email alerts
|

Effect of unilateral cryptorchidism on mobility and velocity parameters of sperm in (Bos frontalis) semen

Abstract: KEYWORDS Mithun CryptorchidComputer assisted sperm analysis Motility Velocity parameters ABSTRACTThe present study was conducted to assess the motility and velocity parameters of sperm of normal intact and unilateral cryptorchid mithun bull by computer assisted sperm analyzer (CASA). Twenty ejaculates were collected from cryptorchid (n=10) and normal intact (n=10) bull. The different parameters assessed through CASA were static sperms (SM), Total Motility (TM), forward progressive motility (FPM), Average Path … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…In Mithun, vaccination against foot and mouth disease significantly affects semen production and its quality profiles; therefore, the semen collection withholding period is standardized as 2.50 months (Perumal, 2018e; Perumal, Khate, & Rajkhowa, 2013). Unilateral cryptorchidism (Perumal, 2013; Perumal, Chang, Sangma, Khate, & Saminathan, 2016) and scrotal insulation (Perumal, 2018f) have a significant adverse effect on scrotal and testicular biometrics, hormones and semen production and its quality profiles in Mithun; therefore, cryptorchid male and semen collection throughout summer season need to be avoided. Vices such as spontaneous erection and masturbation have non‐significant adverse effects on semen production and its quality profiles in Mithun (Perumal, Vupru, Khate, Veeraselvam, et al, 2013).…”
Section: Applications Of Arts In Mithunmentioning
confidence: 99%
“…In Mithun, vaccination against foot and mouth disease significantly affects semen production and its quality profiles; therefore, the semen collection withholding period is standardized as 2.50 months (Perumal, 2018e; Perumal, Khate, & Rajkhowa, 2013). Unilateral cryptorchidism (Perumal, 2013; Perumal, Chang, Sangma, Khate, & Saminathan, 2016) and scrotal insulation (Perumal, 2018f) have a significant adverse effect on scrotal and testicular biometrics, hormones and semen production and its quality profiles in Mithun; therefore, cryptorchid male and semen collection throughout summer season need to be avoided. Vices such as spontaneous erection and masturbation have non‐significant adverse effects on semen production and its quality profiles in Mithun (Perumal, Vupru, Khate, Veeraselvam, et al, 2013).…”
Section: Applications Of Arts In Mithunmentioning
confidence: 99%
“…Thus, Cryptorchidism has been associated with abnormal testicular structure and functions [9]. Some studies have reported sperm abnormalities in bucks [7] [8] [10] and other male species [11] [12] [13] with unilateral cryptorchidism.…”
Section: Introductionmentioning
confidence: 99%